Effect of Graphene Fillers on the Mechanical Properties of Kenaf-Fibre Reinforced Polypropylene Composites - Nur Izzati Zulkarnain; Izdihar Tharazi; Mohamad Nazrin Hazim Ahmad Faiesal; Ramli Junid; Abdul Hakim Abdullah (International Journal of Integrated Engineering, 2026)
This study investigated the influence of graphene nanoplatelet fillers on the mechanical performance of kenaf fibre reinforced polypropylene composites. Composites were fabricated with varying weight proportions of polypropylene matrix, kenaf fibre, and graphene with composition ratios of 90-10, 90-9.5-0.5, 90-9.0-1.0, and 90-8.5-1.5. Composite samples were fabricated using a hot-press compression moulding at 180°C. Thermal characterisation of each kenaf fibre, graphene and polypropylene was conducted using thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). The produced composites were then subjected to tensile, flexural and impact testing. Thermal analysis: TGA and DSC revealed that graphene exhibited excellent thermal stability with no significant weight loss. In contrast, kenaf fibre showed typical degradation associated with the decomposition of its structural components. The melting point of polypropylene was confirmed at approximately 165°C. Mechanical evaluation showed that the composition with 1.5 wt.% graphene (90-8.5-1.5 specimen) exhibited the highest tensile strength (21.9 MPa), flexural strength (24.6 MPa), and impact strength (22.8 J/m2). The enhanced mechanical properties are caused by the improved fibre-matrix interfacial bonding facilitated by the inclusion of graphene in the composites. The outcomes of this study offer a sustainable solution for automotive and load-bearing applications.